ECOLOGICAL STATE ASSESSMENT OF AQUACULTURE PONDS BASED ON PHYTOPLANKTON - I. Hrytsyniak; T. Grygorenko; A. Bazaeva; N. Chuzhma (Ribogospodarsʹka Nauka Ukraïni, 2014)
Purpose. Assessment of the ecological state of aquaculture ponds based on phytoplankton indices when using different organic fertilizers.